Understanding basic snatch techniques for beginner weightlifters PABSI Aceh - Is, Zulheri; Sarwita, Tuti (Jurnal Ilmu Keolahragaan, 2022)
Weightlifting is a sport that competes to lift heavy weights called barbells, which is performed with a combination of strength, flexibility, concentration, ability, discipline. The formulation of the problem in this study is the need for good and correct mastery of the basic snatch force technique in weightlifting. The purpose of this study was to analyze the basic techniques of the snatch style and to analyze the initial to late movements of the snatch technique, in Aceh Weightlifting Athletes. This research is a qualitative research using survey method. The population in this study was beginner athletes at the Seuramoe Lifter Aceh weightlifting club with a total sample of 5 athletes, the total sampling technique was sampling.The research states that from the analysis of the Star Position, First Pull, Transition, and Scond Pull movements, with the correct movement position, the average movement of the Seuramoe lifter Aceh Club weightlifter has not seen the Star Position, First Pull, Transition, and A good Scond Pull is in accordance with the research guidelines with a 75% safety percentage. The movements are carried out correctly.